Analisis Kompetensi Kepribadian Guru SD di Era Society 5.0 - Lisnawati Nurhasanah; Tetep Tetep; Muhammad Nurjamaludin (Institut Pendidikan Indonesia, 2023)
A teacher is said to be a professional teacher if he has inherent competence personality. Personality that is commonly known to be very abstract. This is encouraging researchers to study further about the personality competence of elementary school teachers through research. The focus of this research is to try to uncover the personality competencies of teachers in the era of society 5.0, and the teacher's efforts to improve his personal competence. This study uses a qualitative approach with a phenomenological method where the subject is school teachers base. Based on the results of the study, it was concluded that the personality competencies of the teachers were solid and stable, capable of being mature, wise and wise in acting, authoritative and being role models for their students. In this era of society 5.0, teachers can balance between IMTAQ and science and technology. Schools and teachers always try to improve their personality competencies through foundation and head coaching activities schools, tahsin training, workshops and independent curriculum IHT.